Perspektif Teknologi Terhadap Peningkatan Pendapatan Petani Di Desa Terasa Kabupaten Sinjai - Abdullah Abdullah; Sabirin Iskandar; Ikrayani Ikrayani (Jurnal Online Manajemen ELPEI, 2022)
This study aims to determine the income level of farmers with a technological perspective (social media) in Terasa Village, Sinjai Regency. This type of research uses a quantitative type, while the sample taken is 30 farmers. The simple linear regression analysis technique used in this study is validity test, reliability test, and hypothesis testing. The results of this study have been tested for validity with the smallest score of the purchase intention indicator, namely 0.384 and the highest score of the brand image indicator variable (X) from a technological perspective is 0.767 declared valid and with the smallest score of return on capital indicator 0.362 and the highest score of the income variable skill and persistence indicator (Y), namely 0.720, is declared valid. The results of the reliability test (X) from a technological perspective are 0.661 and the reliability of the income variable (Y) is 0.629 with both variables exceeding Cronbach Alpha > 0.6 so that the research is said to be reliable or feasible to continue. The results of this study indicate that the technology perspective variable (X) with the brand image indicator and the income variable (Y) with the persistence and expertise indicators has a positive and significant effect on increasing farmers' income, meaning that people who sell online with various brand images and it is with this skill and persistence that their income increases.